The Effect of Digital Transformation on the Islamic Financial Sector: A Study on the 11 Largest Halal Industry Countries in 2018-2022 - Hakim, Lukman; Rizaldi, Muhammad; Syahrin, Fira Alfi; Shofiatin, Nanik; Zhahirah, Nasywa (Universitas Pendidikan Ganesha, 2024)
Islamic finance is an important instrument in offering crucial support for the resilience of global economy after the failure of the capitalist economic system in 1998. The institutions showed good ability and sustainability during a period marked by negative trends in conventional banks. The halal industry, as an aspect with a major influence on the growth of Islamic finance, was considered inseparable from the role of digitalization. This was evidenced by the achievement of a world economic output of USD 193 billion through job creation to drive global growth. In addition, important instruments in digitalization with a major impact on the economy played a significant role in the growth of the sector. Therefore, this research aimed to determine the influence of the determining factors shaping the relationship between digital economy and Islamic finance. A quantitative approach was adopted through panel data regression analysis to examine digital instruments within 11 of the world's highest halal industrial countries. The results showed that valuable input for the government and financial institutions in developing strategies and policies for the growth of Islamic finance was provided through digital economy. In this context, appropriate policies were designed to facilitate innovation and growth by understanding the influence of the digital economy.